Recipes for science an introduction to scientific methods and reasoning - Potochnik, Angela; Colombo, Matteo; Wright, Cory 1975- (Routledge, 2019)
Today, scientific literacy is an essential aspect of any undergraduate education. Recipes for Science responds to this need by providing an accessible introduction to the nature of science and scientific methods, reasoning, and concepts that is appropriate for any beginning college student. It is designed to be adaptable to a wide variety of different kinds of courses, such as introductions to scientific reasoning or critical thinking, philosophy of science, and science education. In any of these different uses, the book helps students better navigate our scientific, 21st-century world. Key Features: Contemporary and historical examples of science from many fields of physical, life, and social sciences. Visual aids to clarify and illustrate ideas. Text boxes to explore related topics. Plenty of exercises to ensure full student engagement and mastery of the information. Annotated 'Further Reading' sections at the end of each chapter. Final glossary with helpful definitions of key terms. A companion website with author-developed and crowdsourced materials, including syllabi for courses using this textbook, bibliography of additional resources and online materials, sharable PowerPoint presentations and lecture notes, and additional exercises and extended projects
Keywords: Wissenschaft; Methode; Science / Methodology; Philosophy; Science / Philosophy